Local versus Central Assessment of Venographies in a Multicenter Trial on the Prevention of Deep Vein Thrombosis in Neurosurgery - Rossi, Romina; Agnelli, Giancarlo; Taborelli, Piera; Fioroni, Claudio; Zerbi, Daniela; Pattacini, Pietro; Giugni, Enrico; Bagatella, Paola; Vaccarino, Antonella (Thrombosis and Haemostasis, 1999)
Venography is the diagnostic method of choice for end-point measurement in multicenter trials on the prevention of postoperative deep vein thrombosis (DVT). The aim of the study was to determine the inter-observer agreement between the local and central assessment of venographies in a multicenter trial comparing enoxaparin and placebo in the prevention of DVT after elective neurosurgery.The study was run in seven centers experienced in venography trials on DVT prevention. The central and local adjudication panels were both blind with respect to the assigned treatment. The central panel was unaware of the local adjudication. Venographies were adjudicated as positive, negative or inadequate for adjudication and positive venographies as proximal or distal DVT. Inter-observer agreement was assessed according to the Cohen’s inter-observer variability index (K index).All 266 venographies (8 monolateral) were considered adequate for adjudication by both the central and local panels. A disagreement was found in 25 cases; K index = 0.75. Fourteen venographies adjudicated as negative centrally were considered positive locally (3 were proximal DVT). Eleven venographies adjudicated as positive centrally (1 was a proximal DVT) were considered negative locally. Enoxaparin was found to be more effective than placebo according to both the central and local adjudication: 16.9% versus 32.6% (Relative risk, RR = 0.52; CI95% 0.33-0.82) according to central adjudication; 18.5% versus 33.3% (RR = 0.56; CI95% 0.36-0.87) according to local adjudication.We conclude that a good inter-observer agreement in the assessment of venography was observed between the central and local adjudication in a study on DVT prevention run in a restricted experienced study framework. The cost and work overloading of central assessment of venographies in this study framework seems not to be justified.
Keywords: Venography; inter-observer agreement; deep vein thrombosis; venous thromboembolism; neurosurgery